Restrictions on cross-border data flows - Martina F. Ferracane (European Centre for International Political Economy (ECIPE), 2017)
Strict privacy regimes, requests to use local data centres and outright bans to transfer data abroad are a few examples of policies imposed recently that restrict data from crossing national or regional borders. This paper is the first one to propose a comprehensive taxonomy of these restrictions, which has a bearing on international trade law.Restrictions on cross-border data flows may affect countries' legal commitments under various trade agreements, including the General Agreement on Trade in Services (GATS). This taxonomy can be the basis of further legal and economic research to assess the legitimacy and necessity of these under international trade law.
Keywords: 330